2018
DOI: 10.1080/03069885.2018.1506567
|View full text |Cite
|
Sign up to set email alerts
|

Avatar-based counselling for psychological distress in secondary school pupils: pilot evaluation

Abstract: This study is a pilot evaluation of a new avatar-based therapeutic tool, ProReal, with psychologically distressed young people within a school setting. In total, 54 young people, aged 12-18 years old, participated in face-to-face avatar-based counselling. Young people used the software to represent themselves and others, their problems and emotions. The primary outcome measure was the Young Person's CORE (YP-CORE). The avatar-based counselling intervention was feasible to implement and acceptable to clients, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…Feedback suggested that the externalization of internal thoughts, feelings and experiences helped the young people express how they were feeling. Although we are limited in reporting findings from two cases, their experiences align with those from previous research into avatar‐based counselling (Cooper et al., ; Rehm et al., ; van Rijn et al., , ). A key theme from this research centred around the software allowing young people to express themselves outside of ‘just using words all the time’ (van Rijn et al., ).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Feedback suggested that the externalization of internal thoughts, feelings and experiences helped the young people express how they were feeling. Although we are limited in reporting findings from two cases, their experiences align with those from previous research into avatar‐based counselling (Cooper et al., ; Rehm et al., ; van Rijn et al., , ). A key theme from this research centred around the software allowing young people to express themselves outside of ‘just using words all the time’ (van Rijn et al., ).…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, the therapy was carried out by one highly experienced clinical psychologist and our results may not reflect the skills of other therapists. Previous research has also shown that reductions in psychological distress tend to be associated with more time spent training with ProReal (Cooper et al., ). Our results may therefore also reflect PS's specific ProReal training.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…To investigate the use of images in therapy, we drew one case from an evaluation study (Cooper, Van Rijn, & Chryssafidou, ; van Rijn, Cooper, & Chryssafidou, ) of a proprietary video game‐like tool developed for therapy and coaching, which we call avatar software. The software allows clients to create digital visual representations of their inner worlds, and life situations, including avatars (virtual people) representing themselves and others.…”
Section: Introductionmentioning
confidence: 99%